Classification of Haplogroup F in Chinese Population of Peninsular Malaysia - Ismail, Siti Balkiah (Universiti Sains Malaysia, 2006)
mtDNA is passed from one generation to the next, essentially unchanged, solely through the maternal line of a family. A total of 44 samples were randomly collected from USM Kampus Kesihatan, Kubang Kerian, Ketantan. mtDNA was extracted from the buccal swabs. All samples were subjected to PCR by using a set of primer, 12233-F and 12630-R to amplify a 397 bp fragment of mtDNA coding region. This fragment was then digested using Hinc II enzymes for determination of the Hinc II site loss or site gain at nucleotide position 12406 for all samples. Samples which did not cut by the Hinc ll enzymes were classified into the F haplogroup. Only 2 samples which are 4.5 % from 22 samples analysed were found to belong to haplogroup F.